Behind the Pesantren Law; Between Recognition and Politicization of Pesantren in Indonesia - Iskandar, Arip Dwi; Ubaidillah, Ubaidillah; Ansori, Miswan; Muthoin, Muthoin (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
This research aims to analyze the dynamics and implications of the Pesantren Law Number 18 of 2019 on the life of Pesantren in Indonesia. This law is considered a form of state recognition of the existence of Pesantren, but it has also triggered a polemic regarding the politicization of Pesantren. This research uses a qualitative approach with a case study method, exploring in-depth related issues. The main data sources are trusted online news and related official documents. The research results show that the Pesantren Law is an effort for state recognition, but also opens up opportunities for excessive intervention. Various parties have various views regarding the implementation of this law. This research contributes a theoretical understanding of the dynamics of the relationship between the state and Pesantrens, as well as its implications for public policy, Islamic politics, and the sociology of religion. Practically, the results of this research can provide input for the government, Pesantren institutions, and other stakeholders in responding to the implementation of the Pesantren Law.